Hipercolesterolemia de la población de 30 a 65 años de edad del barrio de Namirez Y Nambija Bajo en el año 2014. - Granda Romero, Yexenia Janeth (2015)
Hypercholesterolemia is full of negative connotations associated with poor diet, sedentary lifestyle, age, race, chronic diseases, alcohol intake and snuff leading to cerebrovascular, cardiovascular and obesity problems, the important is to know what it is, how it works and when it harmful to health. This research was framed in a study realized in the neighborhoods Namirez and Nambija Bajo during the period February to December 2014 with the aim of identifying values hypercholesterolemia population of 30-65 years old and based on the results draw an intervention proposal that would help improve lifestyles. As data collection technique survey within the community under study, data were processed by computerized means and percentage was used in the statistical analysis was applied. The variables used were selected in correspondence with the scientific problem. The results are reflected in tables designed for that purpose and reached the following conclusions: the group most affected age was 30-40 years and the female, it was shown that patients who have risk factors and family history of hypercholesterolemia have a higher chance of developing this disorder, encountering higher incidence total cholesterol borderline high risk. I finally was planned and executed the proposed intervention to improve the lifestyles of the population Keywords: Cholesterol, Hypercholesterolemia, adult and young population